English Language Acquisition: A Literature Review of Recent Research Trends and Learning Processes - Suhria Suhria; Uswatun Hasanah (Scolae: Journal of Pedagogy, 2026)
This study aimed to identify research trends, learning processes, and factors influencing English Language Acquisition (ELA) based on Scopus-indexed publications from 2021 to 2026. A literature review method was employed using articles retrieved from the Scopus database with the keyword “English Language Acquisition.” The search was limited to journal articles, open-access publications, and studies published between 2021 and 2026. A total of 17 articles that met the inclusion criteria were analyzed through thematic analysis. The findings revealed five major themes: phonological acquisition, morphosyntactic acquisition, vocabulary development, cognitive factors, and instructional interventions. Phonological acquisition emerged as the most dominant area, emphasizing the influence of first-language systems on second-language speech perception and production. The review also demonstrated that cognitive factors, including memory and auditory processing abilities, significantly contribute to language learning outcomes. Furthermore, multimodal learning environments and technology-supported instruction were found to facilitate language development. Overall, the findings indicate that English language acquisition is a multidimensional process shaped by the interaction of linguistic, cognitive, perceptual, and environmental factors.